(untitled) (XXI Century. Spanish Literature and Culture, 2004)
Lutheranism, a divided society and the recuperation of the so called ‘historic memory’ can all act as an underlying axis for the main character of Delibes’ novel, El hereje, creating a man whose life is marked by his orphanhood, which unleashes the hate his father feels for him, and the unrequited love for his nursemaid. At his adulthood, trade, marriage and a series of decisions move him to take part in a sect which follows the protestant currents that are secretly penetrating that Spain at the time and which, in time, will cause his death.